Phylogenetic Patterns of Swainsonine Presence in Morning Glories - Quach, Quynh N.; Gardner, Dale R.; Clay, Keith; Cook, Daniel (Frontiers in Microbiology, 2022)
Endosymbionts play important roles in the life cycles of many macro-organisms. The indolizidine alkaloid swainsonine is produced by heritable fungi that occurs in diverse plant families, such as locoweeds (Fabaceae) and morning glories (Convolvulaceae) plus two species of Malvaceae. Swainsonine is known for its toxic effects on livestock following the ingestion of locoweeds and the potential for pharmaceutical applications. We sampled and tested herbarium seed samples (n = 983) from 244 morning glory species for the presence of swainsonine and built a phylogeny based on available internal transcribed spacer (ITS) sequences of the sampled species. We show that swainsonine occurs only in a single morning glory clade and host species are established on multiple continents. Our results further indicate that this symbiosis developed ∼5 mya and that swainsonine-positive species have larger seeds than their uninfected conspecifics.